(untitled) - Bishop, Paul L. (Boston, MA, 2000)
Topics in this text include: properties and fates of environmental contaminants; industrial activity and the environment; enironmental regulations; life-cycle assessment; pollution prevention planning; design for the environment; residuals management; and fugitive emissions.
Keywords: Factory and trade waste,Pollution prevention; Management